PENGARUH STRES DAN KETERLIBATAN KERJA TERHADAP PRESTASI KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING PADA PT. CIPUTRA INTERNASIONAL CABANG MANADO - MANUEKE, DEBORA (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
Performance is a workly achievement or working result/output either the quality or quantity gained by a personal in every certain period with in doing his/her duty as his/her responsibility given. In fact, the employee performance is influenced by many things. Some of these things observed by the writer are the job stress, job involvement and job satisfaction at the employee of PT. Ciputra Internasional Cabang Manado. The research aims at knowing the significant influence of stres , job involvement and job satisfaction to performance, knowing the signigicant influence of stress to performance if it is moderated withÂ  job satisfaction and knowing the significant influence of job involvemen if it is moderated by the job satisfaction.The result of the research shows that stres significantly related to performance in negative direction while job involvment variable give a positive influence to the performance. From the result also found that job satisfaction moderates the relationship between stres and performance in a positive direction and between job involvement and performance the effect of job satisfaction will weakend the relationship of job involvement and performance. Based on the regression result, it shows that adjusted R square is 0.448. So that it can be interpreted that stress (X1), job involvement (X2), job satisfaction (X3), interaction between stres and job satisfaction (M1) and interaction between job involvement and job satisfaction (M2) influenced the performance of the employee 44.8% while the rest of 55.2% employee performance is influenced by other variable which is not observed in this research. Â  Keywords : stress, job involvement, job satisfaction, performance